2018
DOI: 10.1002/2017ja025019
|View full text |Cite
|
Sign up to set email alerts
|

MMS Observation of Asymmetric Reconnection Supported by 3‐D Electron Pressure Divergence

Abstract: We identify the electron diffusion region (EDR) of a guide field dayside reconnection site encountered by the Magnetospheric Multiscale (MMS) mission and estimate the terms in generalized Ohm's law that controlled energy conversion near the X‐point. MMS crossed the moderate‐shear (∼130°) magnetopause southward of the exact X‐point. MMS likely entered the magnetopause far from the X‐point, outside the EDR, as the size of the reconnection layer was less than but comparable to the magnetosheath proton gyroradius,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 45 publications
(180 reference statements)
7
50
0
Order By: Relevance
“…Detection of electron‐scale current sheets in Earth's magnetic environment has become possible with the high‐resolution instrumentation onboard the Magnetospheric Multiscale (MMS) spacecraft, which can resolve electron skin depth ( d e ) scale, filamentary currents narrower than the spacecraft separation (Phan et al, ; Phan et al, ; Yordanova et al, ; Wilder et al, ). Current sheets with thicknesses on the order of a few d e are often observed in association with the electron diffusion region (EDR) and separatrix regions of magnetic reconnection (Burch et al, ; Chen et al, ; Chen et al, ; Genestreti et al, ; Norgren et al, ; Torbert et al, ; Torbert et al, ; Wang et al, ; Webster et al, ). Recent studies have shown that thin current sheets and their associated electron crescent distributions can result purely as a manifestation of diamagnetic effects (Egedal et al, ; Rager et al, ), though these are typically found in regions where there is significant dissipation (Eriksson et al, ; Torbert et al, ; Genestreti et al, ; Wilder et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Detection of electron‐scale current sheets in Earth's magnetic environment has become possible with the high‐resolution instrumentation onboard the Magnetospheric Multiscale (MMS) spacecraft, which can resolve electron skin depth ( d e ) scale, filamentary currents narrower than the spacecraft separation (Phan et al, ; Phan et al, ; Yordanova et al, ; Wilder et al, ). Current sheets with thicknesses on the order of a few d e are often observed in association with the electron diffusion region (EDR) and separatrix regions of magnetic reconnection (Burch et al, ; Chen et al, ; Chen et al, ; Genestreti et al, ; Norgren et al, ; Torbert et al, ; Torbert et al, ; Wang et al, ; Webster et al, ). Recent studies have shown that thin current sheets and their associated electron crescent distributions can result purely as a manifestation of diamagnetic effects (Egedal et al, ; Rager et al, ), though these are typically found in regions where there is significant dissipation (Eriksson et al, ; Torbert et al, ; Genestreti et al, ; Wilder et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in National Aeronautics and Space Administration's Magnetospheric Multiscale (MMS) mission (Burch et al, 2015), electron VDFs with a crescent shape have been detected as evidence of fast reconnection Chen, Hesse, Wang, Gershman, et al, 2016;Chen et al, 2017;Genestreti et al, 2017Genestreti et al, , 2018Norgren et al, 2016;Phan et al, 2016;Rager et al, 2018). For example, in National Aeronautics and Space Administration's Magnetospheric Multiscale (MMS) mission (Burch et al, 2015), electron VDFs with a crescent shape have been detected as evidence of fast reconnection Chen, Hesse, Wang, Gershman, et al, 2016;Chen et al, 2017;Genestreti et al, 2017Genestreti et al, , 2018Norgren et al, 2016;Phan et al, 2016;Rager et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In space observations such as in Earth's magnetosphere, velocity distribution functions (VDFs) for ions and electrons provide us useful information about the physics working on local plasmas. For example, in National Aeronautics and Space Administration's Magnetospheric Multiscale (MMS) mission (Burch et al, 2015), electron VDFs with a crescent shape have been detected as evidence of fast reconnection Chen, Hesse, Wang, Gershman, et al, 2016;Chen et al, 2017;Genestreti et al, 2017Genestreti et al, , 2018Norgren et al, 2016;Phan et al, 2016;Rager et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The relative importance of the terms in Equation (1) and of the EED measures in Equations (2-4) have been studied both numerically and experimentally at reconnecting current sheets (Hesse et al, 2016;Nakamura et al, 2016;Shay et al, 2016;Torbert et al, 2016b;Genestreti et al, 2018). According to these event studies, E ′ (left hand side of Equation 1) dominates outside the reconnection diffusion region, where both electrons and ions are attached to the magnetic field, and the right hand side of the Equation (1) is negligible.…”
Section: Discussionmentioning
confidence: 99%
“…Inside the electron diffusion region, where both ions and electrons are demagnetized, the terms on the right hand side of Equation (1) balance E ′ and the first term on the right, (∇.P e ), is much larger than the second inertial term. However, near the reconnection X-line the inertial term can reach half of the pressure divergence term (Genestreti et al, 2018). Since the probability of crossing multiple reconnection X-lines in the magnetosheath is low, the inertial term can be neglected.…”
Section: Discussionmentioning
confidence: 99%